The COPII subunit MoSec24B is involved in development, pathogenicity and autophagy in the rice blast fungus - Qian, Hui; Sun, Lixiao; Wu, Minghua; Zhao, Wenhui; Liu, Mengyu; Liang, Shuang; Zhu, Xueming; Li, Lin; Su, Zhenzhu; Lu, Jianping; Lin, Fucheng; Liu, Xiaohong (Frontiers in Plant Science, 2023)
The endoplasmic reticulum (ER) acts as the starting point of the secretory pathway, where approximately one-third of the proteins are correctly folded and modified, loaded into vesicles, and transported to the Golgi for further processing and modification. In this process, COPII vesicles are responsible for transporting cargo proteins from the ER to the Golgi. Here, we identified the inner shell subunit of COPII vesicles (MoSec24B) and explored the importance of MoSec24B in the rice blast fungus. The targeted disruption of MoSec24B led to decreased growth, reduced conidiation, restricted glycogen and lipids utilization, sensitivity to the cell wall and hypertonic stress, the failure of septin-mediated repolarization of appressorium, impaired appressorium turgor pressure, and decreased ability to infect, which resulted in reduced pathogenicity to the host plant. Furthermore, MoSec24B functions in the three MAPK kinase signaling pathways by acting with MoMst50. Deletion of MoSec24B caused reduced lipidation of MoAtg8, accelerated degradation of exogenously introduced GFP-MoAtg8, and increased lipidation of MoAtg8 upon treatment with a late inhibitor of autophagy (BafA1), suggesting that MoSec24B regulates the fusion of late autophagosomes with vacuoles. Together, these results suggest that MoSec24B exerts a significant role in fungal development, the pathogenesis of filamentous fungi and autophagy.